Sketsa Hukum Keluarga Islam Dalam Literatur Arab Kontemporer - Slamet Arofik (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Abstract: Islamic Family Law (Ahwal Syakhsiyah) is a set of rules and procedures in the household ranging from pre-marriage, the implementation of marriage to the usual things that occur after marriage. Plus the chapter endowments, wills, grants and inheritance. This paper will explain the sketch and the existence of Islamic Family Law (IPR) in Contemporary Arabic literature. This finds the value of urgency considering that Islamic Family Law in the contemporary period has become an independent and separate study from other fiqh studies although basically Islamic Family Law is part of Jurisprudence. The creativity shown by the mujtahid and the next generation of Islamic thinkers through the means of ijtihad manifests the flexibility of Islamic law, especially IPR and can keep it away from the threat of stagnation which results in Islamic law being like a fossil because it is unable to match the times.